2014
DOI: 10.1155/2014/439146
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antiproliferative Effects of Combinedγ-Tocotrienol and PPARγAntagonist Treatment Are Mediated through PPARγ-Independent Mechanisms in Breast Cancer Cells

Abstract: Previous findings showed that the anticancer effects of combined γ-tocotrienol and peroxisome proliferator activated receptor γ (PPARγ) antagonist treatment caused a large reduction in PPARγ expression. However, other studies suggest that the antiproliferative effects of γ-tocotrienol and/or PPARγ antagonists are mediated, at least in part, through PPARγ-independent mechanism(s). Studies were conducted to characterize the role of PPARγ in mediating the effects of combined treatment of γ-tocotrienol with PPARγ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…The contradictory results might be derived from the cancer cell types used in this experiment; the authors [26] employed breast cancer cells while Campbell et al [79] used prostate cancer cells. They concluded that the synergistic effect between γ-T3 and PPARγ antagonists was mediated through PPARγ-independent mechanisms [80]. …”
Section: Synergistic Anticancer Actions Of T3 and Chemotherapeuticmentioning
confidence: 99%
“…The contradictory results might be derived from the cancer cell types used in this experiment; the authors [26] employed breast cancer cells while Campbell et al [79] used prostate cancer cells. They concluded that the synergistic effect between γ-T3 and PPARγ antagonists was mediated through PPARγ-independent mechanisms [80]. …”
Section: Synergistic Anticancer Actions Of T3 and Chemotherapeuticmentioning
confidence: 99%
“…Thus, tocotrienol displays potent anticancer activity at treatment doses that have little or no effect on the growth and viability of primary epithelial cells isolated from the mammary gland or immortalized mouse (CL-S1) and human (MCF-10A) normal mammary epithelial cell lines [16][17][18]. Additional reports have shown that the combined use of tocotrienols with other chemotherapeutic agents results in a synergistic anticancer response [19][20][21][22][23].…”
Section: γ-Tocotrienol and Cancermentioning
confidence: 99%
“…Furthermore, the use of phytochemicals in the prevention and treatment of cancer has recently gained much interest, and combination therapies are attractive because an additive or synergistic therapeutic response can result. The rationale for using tocotrienols in combination therapy is based on the findings that a form of vitamin E has a broad range of anticancer actions and the principle that resistance to any single agent can be overcome by using multiple agents with complimentary mechanisms of action [11,12,[19][20][21][22][23]40]. Previous studies have shown that combined low dose of γ-tocotrienol with other chemotherapeutic or phytochemical agents displays significantly enhanced anticancer effects, as compared to that of individual treatment alone [11].…”
Section: Combination Treatment Of γ-Tocotrienol With Other Chemotheramentioning
confidence: 99%
“…PPAR gamma is also present in other tissues, such as breast [70,71], colon [72][73][74], lung [75,76], ovary [77,78], prostate [79,80] and thyroid [81,82] wherein it mediates several specific functions, such as early development [83], cell proliferation [84], differentiation [85], apoptosis [86], and metabolic homeostasis [87]. Many investigators [88][89][90][91][92][93][94][95][96][97] reported that PPAR gamma was also involved in the control of transcriptional regulation of autophagy.…”
Section: Newly Participant Of Autophagy Regulation: Pparsmentioning
confidence: 99%